STUDI FENOMENOLOGI: PENGALAMAN IBU MELAHIRKAN DI RUMAH DENGAN KEMITRAAN TENAGA KESEHATAN DAN DUKUN BERANAK DI DESA PERHENTIAN LUAS, KABUPATEN KUANTAN SINGINGI RIAU - Dian Roza Adila; Natsir Nugroho; Idriani Idriani (STIKes Hang Tuah Pekanbaru, 2020)
One indicator to determine the high degree of health of a country showed from maternal mortality (MMR). For some areas that have diï¬ƒcult access to health services, the Ministry of Health makes a policy by developing partnership programs for health workers and tradional birth aendants. The phenomenon of tradional birth aendants becomes an interesng phenomenon because of the values of local wisdom they guard. This study aims to ï¬nd out more about the experience of parcipants at-home birth with a partnership of health workers and tradional birth aendants. The method used with qualitave design with phenomenology approach. Parcipants were determined using Purposive sampling method. Methods of data collecon used in-depth interviews with mothers and FGDs on Kepala Desa, Pemangku Adat, tradional birth aendants, and health workers. The results of this study obtained 6 themes of choice of place and helpers during childbirth, mother beliefs against tradional birth aendants in the process of childbirth, Tradion of manyiria and sequenal during pregnancy and aer childbirth, mother's feelings with partnership, independent task of tradional birth aendants aer childbirth and Ulizaon of health services. Suggeson in this research is health workers must know culture adopted by paent and family cared. It aims to give an overview and posive impact on the enhancement of the quality of maternal health services in the context of culture.